Improvements in direct-current characteristics of Al0.45Ga0.55As-GaAs digital-graded superlattice-emitter HBTs with reduced turn-on voltage by wet oxidation. - Ming-Kwen Tsai
Heterojunction bipolar transistors (HBTs) having an Al0.45Ga0.55As-GaAs digital-graded superlattice (DGSL) emitter along with an InGaP sub-emitter are reported. The band diagram of the DGSL emitter is analyzed by using a transfer matrix method and the theoretical result is consistent with the experimental observation that the DGSL emitter smoothes out the potential spike at the emitter-base junction. Such passivated HBTs with a high Al-fraction passivation layer exhibit a small offset voltage of 50 mV, a turn-on voltage of 0.87 V, and a current gain of 385. The HBTs are examined by wet-oxidizing the exposed passivated region under various conditions. Experimental results reveal that the HBTs with an exposed high Al-fraction emitter are sensitive to the ambient air. However, with InGaP capped upon the high Al-fraction emitter, the HBTs exhibit better oxidation quality. The wet oxidation brings forth the most remarkable improvements for the InGaP-capped HBTs when the passivation layer is totally wet oxidized. Furthermore, some devices from the same chip have undergone nitrogen treatment for comparison.
Keywords: 0.87 V; 50 mV; InGaP; InGaP sub-emitter.; InGaP-capped HBTs; Band diagram analysis; Digitally-graded superlattice emitter; Emitter-base junction; High Al-fraction passivation layer; Offset voltage; Oxidation quality; Passivated HBTs; Potential spike; Transfer matrix method; Turn-on voltage reduction; Wet oxidation; Al0.45Ga0.55As-GaAs.